BUILDING A PSYCHOLOGICAL FLOW SCALE IN THE RHYTHMIC GYMNASTICS LESSON FOR THIRDSTAGE STUDENTS OF THE COLLEGE OF PHYSICAL EDUCATION AND SCIENCES - Mohsin Dhahi, Nuha; Hamzah Shuhaib, Mohammed (International Journal of Psychosocial Rehabilitation, 2020)
In this study, the two researchers try to identify the degree of psychological flow among third-stage students in the College of Physical Education and Sports Sciences/University of Baghdad, by constructing a psychometric flow meter for third-stage students in the College of Physical Education and Sports Sciences/University of Baghdad, and the research sample reached 123 female students They represent 100% of the research community, and after conducting the scientific foundations for building the scale, the two researchers reached the final version of the psychometric flow scale with 21 items with four axes.